Developing a Library Association Membership Survey: Challenges and Promising Themes - Dunne, Mary (Evidence Based Library and Information Practice, 2022)
Objective – Many of us involved in the library and information sector are members of associations that represent the interests of our profession. These associations are often key to enabling us to provide evidence based practice by offering opportunities such as professional development. We invest resources in membership so we must be able to inform those in charge about our needs, expectations, and level of satisfaction. Governing bodies and committees, therefore, need a method to capture these views and plan strategy accordingly. The committee of the Health Sciences Libraries Group (HSLG) of the Library Association of Ireland wanted to enable members to give their views on the group, to understand what aspects of a library association are important to librarians in Ireland, and to learn about the reasons for and against membership.Methods – Surveys are a useful way of obtaining evidence to inform policy and practice. Although relatively quick to produce, their design and dissemination can pose challenges. The HSLG committee developed an online survey questionnaire for members and non-members (anyone eligible to join our library association). We primarily used multiple choice, matrix, and contextual/demographic questions, with skip logic enabling choices of relevance to respondents. Our literature review provided guidance in questionnaire design and suggested four themes that we used to develop options and to analyse results.Results – The survey was made available for two weeks and we received 49 eligible responses. Analysis of results and reflection on the process suggested aspects that we would change in terms of the language used in our questionnaire and dissemination methods. There were also aspects that show good potential, including the four themes that were used to understand what matters to members: expertise (professional development), community (connecting and engaging), profession (sustaining and strengthening), and support (financial and organizational supports). Overall, our survey provided rich data that met our objectives.Conclusion – It is essential that those who are governing any group make evidence based decisions, and a well-planned survey can support this. Our article outlines the elements of our questionnaire and process that didn’t work, and those that show promise. We hope that lessons learned will help anyone planning a survey, particularly associations who wish to ascertain the views of their members and others who are eligible to join. With some proposed modifications, our questionnaire could provide a template for future study in this area.